Study on the Correlation Between Fractal Dimension and Permeability in Shale Reservoir Fracture Networks - Wang, Haoyu (International Journal of Computer Science and Information Technology, 2025)
Shale reservoirs usually show the characteristics of low porosity and low permeability, and the internal natural fractures are generally developed, and their reservoir space and fluid seepage capacity are mainly controlled by complex fracture networks. As the dominant channel for fluid migration in the reservoir, the distribution of natural fractures not only directly determines the accumulation and production of oil and gas, but also has a key impact on the expansion and final transformation of fracture network morphology in the subsequent hydraulic fracturing process. It should be pointed out that such fracture systems often show heterogeneous and self-similar fractal characteristics in terms of spatial distribution. Therefore, the degree of development of the fracture network can be characterized by fractal dimensions. In this paper, the relationship between fractal dimension and permeability of fracture networks is studied by simulating fracture networks of different complexity through the simulation method of discrete fracture networks. The results show that the fractal dimension of shale reservoir fracture network is linearly positively correlated with the number of fractures and the maximum length of fractures. There is also a linear positive correlation between the fractal dimension corresponding to the maximum length and number of fractures and the equivalent permeability of different fractures, and the correlation is good. This discrete fracture network simulation of the natural fracture system of shale reservoirs is not only an important way to understand its reservoir characteristics and seepage mechanism, but also a key link to improve the efficiency of shale oil and gas development and optimize the fracturing design of fracturing.